HUBUNGAN SARAPAN DAN SOSIAL BUDAYA DENGAN STATUS GIZI ANAK SD PULAU SEMAU KABUPATEN KUPANG (RELATIONSHIP BREAKFAST AND SOCIO-CULTURAL WITH NUTRITIONAL STATUS OF CHILDREN ELEMENTARY SCHOOL IN SEMAU ISLAND KUPANG REGENCY) - Maria Helena Dua nita (Persagi, 2016)
Nutritional problems in students are the low energy intake at breakfast. East Nusa Tenggara Province the highest prevalence of under weight of 7,8 pencent in children aged 5-12 years. The study purposes were analyzed the breakfast energy contribution and nutrition socio-cultural to the nutritional status of elementary school students in remote areas of Semau Island. This was observational analytic study used cross sectional design. The subjects were fifth grade of elementary school students in Semau Island Kupang Regency. Subject was taken used random clusters about 112 children. Data were analyzed with chi square test and ordinal regression multivariates. There is relationship of breakfast energy contribution and nutritional status (p = 0.043), there is not relationship of breakfast protein contribution and nutritional status (p=0.918), there is not relationship of eating habits to the nutritional status (p=0.405) there is not relationship of eating refrain and nutritional status (p=0.903), there is not relationship of appetite and nutritional status (p=0,614), there is not relationship of nutrition knowledge and nutritional status (p=0.417), there is not relationship of tribes to the nutritional status (p=0.522). Kupang for district health office, the need to conduct feeding breakfast to be a form of primary school students in Semau Island of Kupang Regency. Masalah gizi pada anak sekolah adalah rendahnya asupan energi pada sarapan pagi. Sarapan pagi anak sekolah sangatlah penting kerena dapat meningkatkan konsentrasi belajar dan stamina. Provinsi Nusa Tenggara Timur adalah daerah dengan prevalensi kurus ( IMT/U) tertinggi (7,8 %) pada anak usia 5-12 tahun. Tujuan penelitian ini untuk menganalisis sumbangan energi sarapan pagi dan sosial budaya gizi dengan status gizi anak SD di daerah terpencil di Pulau Semau. Penelitian ini adalah observasional analitik dengan rancangan potong lintang. Subjek penelitian adalah anak kelas 5 SD di Pulau Semau Kabupaten Kupang. Subjek di ambil dengan menggunakan proporsional random sampling sebanyak 112 anak. Data diperoleh melalui wawancara, pengisian kuesioner dan pengukuran antropometri. Data dianalisis dengan uji chi square dan multivariate regresi ordinal. Hasil menunjukkan ada hubungan sumbangan energi sarapan pagi dan status gizi (p=0,043). Tidak ada hubungan antara asupan protein (p=0,918), kebiasaan makan (p=0,405), pantangan makan (p=0,903), selera makan (p=0,614), pengetahuan gizi (p=0,417), dan suku (0,552) dengan status gizi. Bagi Dinas Kesehatan Kabupaten Kupang perlu mengadakan program pemberian makanan tambahan berupa sarapan pagi bagi anak sekolah dasar di Pulau Semau.